Storage of materials in construction - Pedro Andrés Navarro Mendoza; Ana María De la Ossa Gordon (Formación Estratégica, 2023)
This research aimed to expand the information known about the processes and types of storage of existing materials in the field of construction, the methodology used was made from a previous research on the subject of storage of materials in the construction sector, through scientific journals and institutional databases, information was extracted that helped us to make a reflection on this same topic which led us to create a common thread to build this article. The research gave us as a result a reflection, among the main ones the importance of logistics processes in a warehouse because it can define the good or bad performance of the storage places, therefore, in these processes it is essential to optimize time, organization and effectiveness. Another of the results obtained was that the dimensions of the warehouse and the processes involved are closely related to the scale of the work, being this the one that defines the aforementioned parameters and that they must necessarily be located as close as possible to the work since this also defines primarily the efficiency of this. Thus, it is concluded that all internal and external processes that take place in a materials warehouse on site have a positive or negative influence on the development of construction activities, impacting the development time.